Financial Literacy and Behavior of Indonesian Diaspora Women: A Study of Muslimah Humairah Community in South Korea - Maulidina, Alma Syifa; Deny, Muhammad; Prayoga, Widi; Purnomo, Budi Supriatono; Purnamasari, Imas (Master of Management, Faculty of Economics and Business, Diponegoro University, 2025)
This study aims to analyze the influence of Financial Literacy and Financial Behavior on Financial Stability among Indonesian diaspora women in South Korea, specifically within the Muslimah Humairah Community. Using a quantitative approach and a descriptive-verificative design, data were collected through a structured questionnaire from 88 respondents. The research employed multiple linear regression analysis and tested the classical assumptions, including normality, multicollinearity, heteroskedasticity, and autocorrelation. The results demonstrate that both Financial Literacy and Financial Behavior have a significant positive effect on Financial Stability. Financial Literacy plays a more dominant role, with a standardized coefficient (Beta) of 0.783, compared to Financial Behavior, which has a Beta of 0.173. The regression model explains 79.4% of the variation in Financial Stability (R² = 0.794), confirming its robustness. These findings highlight the importance of integrating financial education with practical behavioral interventions to foster economic resilience. Improving financial knowledge and encouraging disciplined financial habits can empower diaspora women to achieve greater financial stability, particularly in the face of economic challenges in a foreign country.